Governing a shared, critical biodiversity landscape through crossborder dialogue platform - Tanui, Joseph; Koech, Grace; Catacutan, Delia (World Agroforestry Centre, 2018)
In this policy brief, we propose an integrated landscape management approach, and creation of a cross-border multistakeholder platform to improve the governance of the Tana-Kipini-Badana bushland and seascapes of Kenya and Somalia.